2018
DOI: 10.3390/su10030821
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation Modes of Operations and Financing in a Low-Carbon Supply Chain

Abstract: Abstract:With the significant increase of fossil energy consumption and the ever-worsening pollution of environment, low-carbon development becomes an inevitable choice. Carbon finance can help firms alleviate the finance pressure from carbon emission reduction. This research explores two financing methods, delay-in-payment and bank loan; and two cooperation decisions, carbon emission reduction cooperation and price cooperation. Four scenarios are considered: non-cooperation, partial-cooperation delay-in-payme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 40 publications
(21 reference statements)
0
27
1
Order By: Relevance
“…Jing et al [37], Cai et al [38], and Kouvelis and Zhao [39] found that firms' financing mode selection decisions are determined by factors such as production cost, capital market competition degree, and enterprise credit rating, respectively. Yang et al [40] compared delay-in-payment and supply chain carbon finance; they found that a supply chain carbon finance pattern can help increase the emission-reduction rate of the whole supply chain. As we can see, most studies on supply chain finance are primarily aimed at the traditional supply chain, with little research on the impact of capital constraint on the low-carbon supply chain.…”
Section: Capital-constrained Supply Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Jing et al [37], Cai et al [38], and Kouvelis and Zhao [39] found that firms' financing mode selection decisions are determined by factors such as production cost, capital market competition degree, and enterprise credit rating, respectively. Yang et al [40] compared delay-in-payment and supply chain carbon finance; they found that a supply chain carbon finance pattern can help increase the emission-reduction rate of the whole supply chain. As we can see, most studies on supply chain finance are primarily aimed at the traditional supply chain, with little research on the impact of capital constraint on the low-carbon supply chain.…”
Section: Capital-constrained Supply Chainmentioning
confidence: 99%
“…As climate change has become more visible in recent years, SMEs are starting to feel greater regulatory and social pressure to adopt environmental strategies [40]. Enterprises' capital flow seriously affects their operation and management.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…Based on a fuzzy multi-criteria evaluation method combined with Topsis, Liang et al [36] propose a new SME financing evaluation model. Yang et al [37] develop four models on the basis of two cooperation models to discuss the firm's carbon emission reduction decisions. They find that compare with other modes, the SCCF pattern can not only increase member's profits, but also achieve effectively control the total carbon emissions.…”
Section: Integrated Management Of Operation and Financementioning
confidence: 99%
“…Besides the literature in Section 2.3, our study further fills this gap. Unlike in previous work [38,39], we concentrate on bank credit financing. The second contribution in this study is the innovation of coordinating mechanism.…”
Section: Low Carbon Supply Chain With Capitalmentioning
confidence: 99%
“…They did not consider the low carbon policies and emission reduction target. By contrast, in a capand-trade policy, Cao and Yu [38] concentrated on trade credit financing, whereas Yang et al [39] focused on carbon financing. The former found that the manufacturer prefers to cooperate with a medium rich retailer, and a general coordinating contract (including revenue sharing, buy back, and quantity discount) can coordinate the supply chain.…”
Section: Low Carbon Supply Chain With Capitalmentioning
confidence: 99%